Penerapan Metode Simple Additive Weighting (SAW) dalam Rekomendasi Calon Ketua Badan Eksekutif Mahasiswa (BEM) - Trisman Andika Hulu; Martua Raja Siregar; Darma Setiawan Putra; Perani Rosyani; Mesran Mesran (ADA Research Center, 2023)
Within the scope of intra-campus students in a university, BEM has an important role as a body that represents students in the form of aspirations and social service. The election of the BEM chairman was the first to be carried out using the voting method by the DPM (Student Representative Council) accompanied by lecturers, so it is very likely that the election results will be less efficient and effective. Therefore, an assessment system is needed to help select recommendations for prospective BEM chairpersons at the university. The right system to overcome this problem is the Decision Support System (DSS). Based on the results of the tests that have been carried out, the best alternative value that meets the criteria as a recommendation for the BEM chairman candidate is alternative A1 in the name of Trisman Andika Hulu with the best preference value of 0.9793 as the first rank.